Stress and flexibility analysis for the rerating of a piping system - Foo, Lai Thutt. (2009)
The objective of this project is to perform stress and flexibility analysis for rerating a 8" diesel feed piping line, running some 1,400 feet at the Esso Singapore refinery, for operation at 500 F and 100 psig, in addition to its original design condition of 325 F and 220 psig. This report covers the analysis of the feed line using the PENGS program, while the exchanger nozzle which the feed line is connected to was analyzed using the FAST2 module of the PEAS program. Both the PEAS and the PENGS programs are Exxon in-house engineering analysis programs.